A Short Introduction - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
For a long time, there has been no journal of short articles on the archaeology of the Ancient Near East. In the way that NABU (Nouvelles Assyriologiques Brèves et Utilitaires) provides up-to-the-minute information for epigraphers, so archaeologists need a forum for the quick exchange of ideas and presentation of results from excavations. Ash-sharq is intended to meet this need. The journal will appear twice a year, this year in April and July.